Edukasi Penerapan Teknologi Bioflok pada Kelompok Pembudidaya Lele di Desa Tengket Arosbaya - Qomariyah, Nor; Triyasari, Sri Ratna; Yunia Sari, Riska Ayu (LPPM Universitas Trunojoyo Madura, 2024)
This article contains a communication strategy for activities socializing cultivation of catfish by using bioflock system on the Jaya Lestari fish farming group, Tengket Village Arosbaya District. Tengket Village has great potential in the field of fisheries where the majority of the people are fishermen. The market demand for catfish is still very high. but has not been able to supply the needs of catfish continuously every day, due to limited land and capital owned. One way that can be done is the cultivation of catfish by using bioflock system. The introduction of bioflock system on fish farming cultivation of